The long-term growth and development of children exposed to Depo-Provera during pregnancy or lactation - Pardthaisong T. (2014)
Children exposed to the injectable contraceptive Depo-Provera (DMPA) during pregnancy (N = 1,207), and/or during breastfeeding (N = 1,215) were exposures during pregnancy or breastfeeding. Weights and heights were measured for all children, and information on signs of puberty obtained for children aged ten and over. Cross-sectional weights and heights by age of DMPA-exposed children were similar to those for controls. Children with DMPA exposure during pregnancy and lactation had an increased risk of suboptimal growth in height, defined as less than two Z scores on NCHS standards (RR = 1.4, 95% CI 1.2-1.8). However, after adjustment for socioeconomic factors by multiple logistic regression, there was no increased risk of impaired growth among the DMPA-exposed children (RR = 1.1, 95% CI 0.8 - 1.6). With the exception of a delay in onset of reported pubic hair growth among DMPA-exposed girls, there were no significant effects on attainment of puberty. We conclude that use of DMPA during pregnancy or breastfeeding does not adversely affect the long-term growth and development of children.